Expanding the Role of Targets in Conservation Policy. (November 2018) - Doherty, Tim S.; Bland, Lucie M.; Bryan, Brett A.; Neale, Timothy; Nicholson, Emily; Ritchie, Euan G.; Driscoll, Don A.
Abstract : Conservation targets perform beneficial auxiliary functions that are rarely acknowledged, including raising awareness, building partnerships, promoting investment, and developing new knowledge. Building on these auxiliary functions could enable more rapid progress towards current targets and inform the design of future targets.